Analisis Penilaian Kinerja Aparatur Sipil Negara (ASN) Di Kantor Kecamatan Karo Kabanjahe - Wirdathun Hasyanah Marbun; Irwan Nasution; Yurial Arief Lubis (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2023)
ASN performance appraisal has a major role in the organization to improve attitudes and positive work practices in achieving employee effectiveness. Providing a good performance appraisal will certainly be useful for related agencies, with this the agency or organization can improve employee performance results for the better. This study is to determine the analysis of ASN assessment at the Kabanjahe District Office, Karo Regency. The type of research used is a qualitative approach that focuses on the assessment of ASN at the Kabanjahe District Office, Karo Regency. The nature of this research is descriptive, the location of this research is carried out at the Kabanjahe District Office Jl. Veteran No.43, Padang MAS, Kabanjahe, Karo Regency, North Sumatra 22111. The results show that it can be concluded that the performance of the State Civil Apparatus in the Karo district office has been good enough, therefore the researchers suggest that there will be no changes in the future. carry out the tufoksi that has been set.